Las cárceles interiores de María de Cazalla: análisis de un proceso inquisitorial - Esteva de Llobet, María Dolores (Estudios Humanísticos. Filología, 1996)
Maria de Cazalla was condemned publicly by the Inquisition in the procceding of the 21th on April, 1529: She was condemned of "iluminist" and "lutheran", alter the Iluminist's Edict (Toledo, 23th on September, 1525). The influence of the book Doctrina cristiana, by Juan de Valdés, and the Erasmu's doctrine was imputed to her. She was accused of heretic practicing of inside devotion that shut out disciplines, fasting, verbal oartion, worship at images and gaze on the cross. She was also accused of dening the free-will and to be a preacher woman.